Comparing three induction chemotherapy regimens for patients with locoregionally advanced nasopharyngeal carcinoma based on TNM stage and plasma Epstein–Barr virus DNA level - Liu, Sai-Lan (BMC Cancer, 2020)
BACKGROUND: We compared the efficacy and toxicity of three IC regimens (TPF: taxanes, cisplatin, and 5-fluorouracil; TP: taxanes and cisplatin; and PF: cisplatin and 5-fluorouracil) followed by CCRT in locoregionally advanced NPC. METHODS: The retrospective study involved 1354 patients with newly diagnosed stage III-IVA NPC treated with IC and CCRT. The median follow-up time in our cohort was 50 months. Based on EBV DNA level, all the patients with stage IV were divided into low- (pre-EBV DNA < 1500 copies) and high-risk group (pre-EBV DNA ≥ 1500 copies). Progression free survival (PFS), overall survival (OS), locoregional relapse free survival (LRFS), distant metastasis free survival (DMFS) and grade 3–4 toxicities were compared among different IC regimens. The survival rates were compared using log-rank test and a Cox proportional hazards model was used to perform multivariate analyses. RESULTS: A multivariate analysis revealed TPF to be more effective than TP. Among stage III patients, no significant difference in clinical outcome between the different IC regimens was showed, while TPF was associated with significantly better survival conditions in the stage IV patients. A further subgroup analysis revealed that only patients with pre-EBV DNA ≥ 1500 copies could benefit from the application of TPF among stage IV NPC. In terms of acute toxicities, PF was associated with fewer grade 3/4 acute toxicities. CONCLUSIONS: In low-risk NPC patients, PF-based IC showed similar efficacy as TPF and TP but was associated with fewer grade 3/4 acute toxicities. In high-risk patients, however, the TPF regimen was superior to PF and TP, although grade 3/4 toxicities were more common with the TPF regimen.